Conservation agriculture in Southern Africa: Advances in knowledge - Thierfelder, Christian L.; Rusinamhodzi, Leonard; Ngwira AR; Mupangwa, W.; Nyagumbo, Isaiah; Kassie, Girma T.; Cairns, Jill E. (Cambridge University Press, 2015)
The increasing demand for food from limited available land, in light of declining soil fertility and future threats of climate variability and change have increased the need for more sustainable crop management systems. Conservation agriculture (CA) is based on the three principles of minimum soil disturbance, surface crop residue retention and crop rotations, and is one of the available options. In Southern Africa, CA has been intensively promoted for more than a decade to combat declining soil fertility and to stabilize crop yields. The objective of this review is to summarize recent advances in knowledge about the benefits of CA and highlight constraints to its widespread adoption within Southern Africa. Research results from Southern Africa showed that CA generally increased water infiltration, reduced soil erosion and run-off, thereby increasing available soil moisture and deeper drainage. Physical, chemical and biological soil parameters were also improved under CA in the medium to long term. CA increased crop productivity and also reduced on-farm labor, especially when direct seeding techniques and herbicides were used. As with other cropping systems, CA has constraints at both the field and farm level. Challenges to adoption in Southern Africa include the retention of sufficient crop residues, crop rotations, weed control, pest and diseases, farmer perception and economic limitations, including poorly developed markets. It was concluded that CA is not a ‘one-size-fits-all’ solution and often needs significant adaptation and flexibility when implementing it across farming systems. However, CA may potentially reduce future soil fertility decline, the effects of seasonal dry-spells and may have a large impact on food security and farmers’ livelihoods if the challenges can be overcome.